Design of Wireless Engine Diagnostic Tool with Raspberry Pi for Learning Media Vocational Education Teacher Candidates - Andri Setiyawan; Suwahyo Suwahyo; Febri Budi Darsono; Sarwi Asri; Fitria Eka Rini; Faizal Agil Arief Setyadi; Doni Puji Laksono; Janahtan Firdaus (Universitas Sultan Ageng Tirtayasa, 2023)
Practical learning is an important activity to improve the skills of prospective vocational education teachers. Supporting facilities have an essential role in the implementation of the practice. This study aims to analyze the learning media's needs for making wireless engine diagnostic tools with raspberry pi. The method used in this research is ADDIE. This research only reached the design stage. This study focuses on the needs analysis used in the development process. The research sample is in the form of an application layout design that will be developed. The instrument in this study was an assessment sheet in the form of a questionnaire regarding the feasibility of the design. Experts in the field of application development assess designs. Developing a wireless engine diagnostic tool with raspberry pi is needed to support learning for prospective vocational teachers. The design of learning media Design of the Wireless Engine Diagnostic Tool with Raspberry Pi can be developed for practical learning of vocational students. The results of the media feasibility test by media experts can be categorized as